Geographers Are Talking—About Waste - Finch-Race, Daniel A.; Jordan, Joanna; Martini, Annaclaudia; Raeymaekers, Timothy (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This piece of conversational co-thinking about waste and its impacts encompasses an array of themes that ranges from physical and conceptual multiplicity to emotional and temporal dimensions of objects/places via economic/political/social values. The format is intended to disturb a certain normativity in scholarship: ideas bubble up spontaneously and hang in the air without necessarily being brought back down to Earth. In point of fact, our ruminations came together through bottom-up conviviality in environments that might seem light-years away from research outputs, not least chatting on a bench in a bustling square during an hour’s lunch break—such shared breathing space is full of potential for slow scholarship.